(untitled) (Economic studies journal, 2018)
This study aimed to recognize of determinants of an agriculture sector growth in Libya (PROD), which represented in a financial aggregate of an agriculture public sector in Libya (FUND); the growth rate of value added of agriculture sector ) VAXGR); an aggregate Libyan exports (AEXPO); & The political and security stability (PS). Farther more, the study was passed on approach of Bound Tests to estimate a relationship in long and short run during 1990- 2017. In additional, the study was found out that there is a long relationship between (PROD) as depended variable and in-depended variables which represented in FUND; VAXGR; AEXPO; &PS, but in short run an absence any relationship among study variables.